Temporomandibular Joint Reconstruction Using Costochondral Graft - Rahman, QB; Molla, MR; Islam, ME (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 225-229 The abstract of this article is available on the PubMed website